P075 Characterisation and structural analysis of a new murine model to study postoperative fibrotic recurrence in Crohn's disease combining ileocecal resection with chronic colitis. (30th January 2023) - Schmidt, K; Li, C; Buck, A; Wilhelm, D; Friess, H; Weber, M C; Neumann, P A
Abstract: Background: The prevention of postoperative fibrotic recurrence in Crohn's disease is still an unsolved problem in the management of patients undergoing bowel resection due to fibrotic intestinal strictures. Appropriate murine models are needed to examine the effect of surgery associated factors as well as mechanical and microbial alterations after ileocecal resection on the development of postoperative fibrotic recurrence in Crohn's disease. Methods: We developed a murine model combining chronic dextrane sodium sulfate(DSS)-colitis with ileocecal resection. 9 to 11-week-old C57BL/6 wild-type mice were exposed to 1% DSS via the drinking water for one week followed by ileocecal resection using a microsurgical technique. After surgery, mice recovered for one week after which two more cycles of DSS-administration were performed, now using 1.5% DSS. Between the two postoperative DSS-cycles one week of recovery was implemented. Histology was performed on the distal ileum, the anastomotic area, the proximal colon, and the distal colon. Results: The inflammation (proximal colon: median score 5 vs. 0; p < 0.001, distal colon: median score 3 vs. 0; p = 0.003) and fibrosis scores (proximal colon: median score 2 vs. 0; p < 0.001, distal colon: median score 2 vs. 0; p = 0.008) were higher in the colon of mice with chronic DSS-colitis compared to mice without colitis. Furthermore, histomorphometric parameters such as the proportionate collagen area (proximal colon: mean area 6.6% vs. 2.6%; p < 0.001, distal colon: mean area 5.4% vs. 3.7%; p = 0.17) and the submucosal thickness (proximal colon: mean 127.4µm vs. 39.7µm; p < 0.001, distal colon: mean 71.5µm vs. 37.2µm; p = 0.049) were significantly higher in mice with chronic colitis. Interestingly, the most profound inflammatory and fibrotic changes were found in the proximal colon compared to the distal colon. No fibrotic changes were found in the small intestine. Conclusion: The combination of ileocecal resection and chronic DSS colitis led to inflammatory and fibrotic changes within the colon. Histopathological features of fibrosis were more prominent in the proximal colon as opposed to the known results from the DSS-colitis model, where inflammatory and fibrotic changes of the intestinal wall worsen towards the distal colon. We thus hypothesize that mechanical and microbial changes due to the altered physiology of the lower gastrointestinal tract after ileocecal resection are responsible for these findings. Continuing research on this model might enable the examination of mechanisms of recurring fibrosis after ileocecal resection in Crohn's disease.